Repositioning Democratic Governance in Africa for Better Dividends Delivery: A Case for Performance - Ikegbu, Ephraim A.; Iwuchukwu, Godwin C.S.P.; Bisong, Peter B. (PREDESTINASI, 2021)
Given the fact that democracy as a system and form of governance which allows for even participation, freedom of expression, rule of law and other indices attached thereto, had awaken the consciousness of humanity from all over the world to key into this form of leadership due to its uncommon benefits. Africa her ‘third world cousins’ seemed to have remained in a slumbering position and have refused to wake up and wear the toga of democratic principles as acts displayed by leaders lacked democratic character. This paper argues that democratic dividends and flavour can be felt and directly impacted on the citizens of Africa especially Nigeria, if adequate political socialization, culturalization and consciousness are fused as part of her cultural education. This new consciousness and democratic mindset will arguably make leaders and the led see each other as an inclusive indispensable part of the whole. It will also eliminate unwantom suspicion, rancour, ethnic bigotry, exclusion and hegemonic display of power and more so, leadership may not be tenured but anchored on performance and service delivery. The paper believes that with a political consciousness, socialization and high sense of political culture, leadership becomes service to the humanity and not business enterprise. Hence leaders that performed optimally may continue to serve the people if they so desire. This paper adopts critical, analytical and expository methods.